2006
DOI: 10.1002/cncr.21701
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine prophylaxis reduces the incidence and severity of hepatitis in hepatitis B virus carriers who receive chemotherapy for lymphoma

Abstract: Objective Metabolic syndrome (MetS) is highly prevalent in rheumatic diseases and is recognized as a new independent cardiovascular risk factor. This study was undertaken to determine the clinical significance of MetS in patients with primary antiphospholipid syndrome (APS). Methods Seventy‐one primary APS patients and 73 age‐ and sex‐matched healthy controls were included. Serum samples were tested for lipid profile, Lp(a), glucose, insulin, thyroid‐stimulating hormone, free T4, erythrocyte sedimentation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 51 publications
3
75
1
4
Order By: Relevance
“…Recent studies have shown that prophylaxis with lamivudine before the initiation of chemotherapy reduces both the incidence and severity of HBV reactivations. [12][13][14][15][16][17][19][20][21][22][23][24][25][26] However, no studies have investigated the use of prophylactic lamivudine in an economic analysis. In this study, we compared the costs and clinical outcomes of 2 different strategies for chronic hepatitis B carriers undergoing chemotherapy for lymphoma treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that prophylaxis with lamivudine before the initiation of chemotherapy reduces both the incidence and severity of HBV reactivations. [12][13][14][15][16][17][19][20][21][22][23][24][25][26] However, no studies have investigated the use of prophylactic lamivudine in an economic analysis. In this study, we compared the costs and clinical outcomes of 2 different strategies for chronic hepatitis B carriers undergoing chemotherapy for lymphoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data from 14 studies published from various parts of the world between 1990 and 2006 that examined HBV reactivation in lymphoma patients undergoing chemotherapy were collected (Table 1). [12][13][14][15][16][17][19][20][21][22][23][24][25][26] Seven of these studies compared the prophylactic use of lamivudine during chemotherapy to the empiric use of the drug, [12][13][14][15][16][17]26 6 studies restricted lamivudine to the treatment of reactivation, [20][21][22][23][24][25] and 1 study examined only the prophylactic use of lamivudine. 19 Lymphoma and Chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It leads to 340,000 liver cancer cases and 500,000 to 1.2 million liver-related deaths each year [2] [3]. China is one of the endemic areas of chronic HBV infection, HBV infection is a common disease, and there are approximately 170 million carriers in China [4]. The incidence of Non-Hodgkin's Lymphoma is increasing rapidly in China, with an annual rise of 1% to 4% [5].…”
Section: Introductionmentioning
confidence: 99%